MANAJEMEN PROYEK PEMBUATAN DASHBOARD UNTUK VISUALISASI CURAH HUJAN DI JAKARTA - Richard; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Project management is a way for organizing to managing and completing projects from start to finish. Using weather data collected from BMKG to carry out data processing by creating a dashboard to display rainfall visualizations using Power BI. This methode research implements use the BI roadmap method. The purpose of this research is to be one of the ways to make decisions. The purpose of the results in this research, it is hoped that making a dashboard visualizations can be useful for users, namely everyone who needs weather information for outdoor activities.